2017
DOI: 10.1007/s10995-017-2372-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Perspectives of African American Medicaid-Insured Women on the Process of Perinatal Care: An Opportunity for Systems Improvement

Abstract: Objectives To address disparities in adverse birth outcomes, communities are challenged to improve the quality of health services and foster systems integration. The purpose of this study was to explore the perspectives of Medicaid-insured women about their experiences of perinatal care (PNC) across a continuum of clinical and community-based services. Methods Three focus groups (N = 21) were conducted and thematic analysis methods were used to identify basic and global themes about experiences of care. Women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
171
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(174 citation statements)
references
References 30 publications
1
171
0
Order By: Relevance
“…In middle/late pregnancy, higher risk was found in Black women and women with lower socioeconomic status. These women may be less likely to get adequate prenatal care 58,59 , perhaps due to perceived discrimination, inability to access providers who take public insurance, and difficulties with transportation [59][60][61][62] . Home-visiting programs may partially solve those problems and improve prenatal care among vulnerable subpopulations 59,63 .…”
Section: Discussionmentioning
confidence: 99%
“…In middle/late pregnancy, higher risk was found in Black women and women with lower socioeconomic status. These women may be less likely to get adequate prenatal care 58,59 , perhaps due to perceived discrimination, inability to access providers who take public insurance, and difficulties with transportation [59][60][61][62] . Home-visiting programs may partially solve those problems and improve prenatal care among vulnerable subpopulations 59,63 .…”
Section: Discussionmentioning
confidence: 99%
“…However, up until now there has been very little focus on missed care in older populations (Zúñiga et al., ). From the patients’ perspective, it has also been identified recently that communities can feel disadvantaged and underserved within the context of community health services (Roman et al., ). This US‐based study identified for example that African Americans availing of Medicaid cover felt marginalised within the community health structures and received suboptimal treatment and health education.…”
mentioning
confidence: 99%
“…10,37,41 Indeed, a 2017 report on AA experiences of discrimination found that one fifth to one third of AAs report that they avoid seeking needed services (e.g., calling the police or medical care) to prevent potential discrimination. 41 Roman et al 40 found that AA women perceived their experiences (provider attitudes, extended wait times, staff facial expressions) across the continuum of clinical and community-based care were influenced by their race and insurance status. It could be that AA women in LIFE who perceived greater experiences of racial microaggressions, in general or in the healthcare setting, develop a sense of hypervigilance and avoid or delay PNC as a way to circumvent potential discrimination.…”
Section: Discussionmentioning
confidence: 99%